2001
DOI: 10.1007/s004150170184
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in multiple sclerosis. A clinical and MRI study in 95 subjects

Abstract: The aim of the present study was to investigate the relationship between involvement of specific areas of the brain and the occurrence of depression and anxiety in patients with multiple sclerosis. We studied 95 patients (62 women and 33 men, mean age 39.5 years, SD 11.2) with definite MS, 97 patients (65 women and 32 men, mean age 40.7, SD 11.9) suffering from chronic rheumatoid diseases and 110 healthy subjects (71 women and 39 men, mean age 40.1, SD 12.7). The disability, the independence, the cognitive per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
126
3
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(150 citation statements)
references
References 41 publications
11
126
3
10
Order By: Relevance
“…Conducting t-tests across the whole sample revealed that males were significantly more depressed and anxious than females, and had significantly lower life satisfaction. Intriguingly, these findings are generally inconsistent with the literature, which tends to show that females (regardless of whether or not they have multiple sclerosis) are more likely to experience mental health problems such as depression and anxiety [4,5].…”
contrasting
confidence: 60%
“…Conducting t-tests across the whole sample revealed that males were significantly more depressed and anxious than females, and had significantly lower life satisfaction. Intriguingly, these findings are generally inconsistent with the literature, which tends to show that females (regardless of whether or not they have multiple sclerosis) are more likely to experience mental health problems such as depression and anxiety [4,5].…”
contrasting
confidence: 60%
“…[32][33][34] The prevalence of clinically significant depressive symptoms is much higher [35] than the prevalence of major depressive disorder, but few studies have evaluated other depressive disorders such as dysthymia. [36] The depressive syndromes associated with MS occur throughout the natural history of the disease, including in patients with very mild forms of MS. [37] Some studies have found associations between depression and severity of MS as reflected by degree of disability [38], but other studies have not replicated these findings. [33,39] The association of depression with the duration of MS illness is also unclear, with most studies finding no correlation [38][39], but others reporting a greater risk of depression in the first year after diagnosis [35] and in patients younger than 35.…”
Section: Major Depressive Disorder Epidemiology and Clinical Corrmentioning
confidence: 99%
“…[36] The depressive syndromes associated with MS occur throughout the natural history of the disease, including in patients with very mild forms of MS. [37] Some studies have found associations between depression and severity of MS as reflected by degree of disability [38], but other studies have not replicated these findings. [33,39] The association of depression with the duration of MS illness is also unclear, with most studies finding no correlation [38][39], but others reporting a greater risk of depression in the first year after diagnosis [35] and in patients younger than 35. [40] Most studies have not found a correlation between depression and female gender among persons with MS. [35,[38][39] …”
Section: Major Depressive Disorder Epidemiology and Clinical Corrmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation with lesion load in the temporal regions has also been suggested [21]. The type of clinical course does not influence the affective or cognitive state of MS patients [22], but depression is one of the strongest predictor of reduced quality of life [23], although as a rule the symptoms respond well to standard treatment [24].…”
Section: Discussionmentioning
confidence: 99%